The Solar Panel Reliability System Is Based On Capacitor Charging Factor - Mahrizal Masri; Zulfadli Pelawi; Hermansyah Alam; Armansyah, Armansyah (Jurnal Info Sains : Informatika dan Sains, 2023)
Electrical energy is a vital sector to meet the needs of a country, especially in Indonesia. This high demand creates many problems for the country. This happens because the DC supply keypoint needs are not yet optimally reliable. This research increases the reliability of keypoints by utilizing solar panels as a source of electrical energy. Solar panels are electricity generation utilizing solar light irradiation into electrical energy using Photovoltaic (PV). Uncertain environmental conditions result in the characteristics of solar panels having an unstable voltage output. The solution to overcome this problem is to use a PID controller and an energy storage system. In this research, a DC supply voltage control system based on a PID Controller for batteries was developed to maintain maximum reliability of the distribution system. Therefore, innovative modification of a system is needed to maximize reliability.